2009
DOI: 10.1103/physrevb.80.085204
|View full text |Cite
|
Sign up to set email alerts
|

Density functional simulations of noble-gas impurities in diamond

Abstract: Noble-gas species are important impurities in the geological analysis of natural diamond and are also used in ion implantation on the basis of chemical inertness. We present the results of density functional simulations of noble-gas atoms in diamond. We show that interstitial species are relatively mobile under geological conditions but require annealing above ϳ700 K for laboratory-based experiments. In addition, with the exception of interstitial helium and neon, the noble-gas atoms are able to react chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
8
17
0
Order By: Relevance
“…This fact is in agreement with the interpretation of the emission as associated to He-V defects, rather than to interstitial He, as proposed in Refs [11,[13][14].…”
Section: Main Textsupporting
confidence: 81%
See 1 more Smart Citation
“…This fact is in agreement with the interpretation of the emission as associated to He-V defects, rather than to interstitial He, as proposed in Refs [11,[13][14].…”
Section: Main Textsupporting
confidence: 81%
“…The need of understanding the possible formation of stable optically active centers, whose current (and still tentative) attribution is based on He incorporation in the diamond lattice, motivates a further investigation of their opto-physical properties. More specifically, the centers have so far been attributed to the He-vacancy complex [13], and density functional theory calculations demonstrated that both this structure and the interstitial He defect could result in stable complexes in the diamond lattice [14]. Apart from this limited body of works, a systematic set of experimental results on the characterization of the opto-physical properties of He-Related (HR, from now on) centers is still missing.…”
mentioning
confidence: 99%
“…On the Fig. 5, one can remark that the H configuration is the saddle point for He and Ne, like in Si [37] or diamond [44]. For Ar the saddle point corresponds to the 4th image, and is not a high symmetry configuration.…”
Section: Migrationmentioning
confidence: 92%
“…Although it is difficult to explain such a large discrepancy, a simple argument would suggest that the migration energy is much lower than 2.5 eV. In fact, previous studies provide He interstitial migration energy of 0.71 eV in silicon [37] and 2.3 eV in diamond [44]. These values are likely to be bounds for the migration in SiC since the energy range of defects in this material is typically between those for silicon and diamond.…”
Section: Migrationmentioning
confidence: 92%
“…According to several independent works the Xe-V defect is the most stable configuration for this impurity in diamond. 14,16,49,50 However, experimental confirmation of this model are yet lacking, since detailed investigations of Zeeman splitting and polarization dependence of photoluminescence of known Xe-related defects do not allow unambiguous selection of a defect model. 51,52 Figure 8a shows a diamond lattice with a Xe-V complex as obtained by QuantumEspresso modelling.…”
Section: Xe In Nanodiamondsmentioning
confidence: 99%